2022
DOI: 10.3390/ijms232113257
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain-Induced Changes in the Expression of Voltage-Gated Potassium Channels in Epithelial Cells Depend on Cell–Cell Contacts

Abstract: Ouabain is a cardiac glycoside, initially isolated from plants, and currently thought to be a hormone since some mammals synthesize it endogenously. It has been shown that in epithelial cells, it induces changes in properties and components related to apical–basolateral polarity and cell–cell contacts. In this work, we used a whole-cell patch clamp to test whether ouabain affects the properties of the voltage-gated potassium currents (Ik) of epithelial cells (MDCK). We found that: (1) in cells arranged as matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 109 publications
(111 reference statements)
0
8
0
Order By: Relevance
“…Specifically, we have described that ouabain (1) boosts intercellular connections facilitated by tight junctions, as proven by an increase in transepithelial electrical resistance (TER), a simultaneous decrease in the movement of dextran between cells, and an increase in the expression of claudins 1, 2, and 4 [13]; (2) induces alterations in adherens junctions, resulting in heightened expression of E-cadherin, β-catenin, and γ-catenin [14]; (3) fosters the enhancement of gap junctional communication among cells forming fully developed epithelial monolayers [15] by modifying the distribution of Cx32 and Cx43 within the membrane [16]; and (4) expedites the recovery of the epithelial phenotype in cells seeded at confluence after trypsinization, as indicated by the presence of an apical cilium in MDCK cells [17]. Apart from its involvement in regulating intercellular contact components, we have found that ouabain also influences the expression of voltage-gated potassium channels, entailing Na + /K + -ATPase acting as a receptor and the engagement of multiple signaling pathways, including cSrc, PI3K, Erk1/2, NF-κB, and β-catenin [18].…”
Section: Introductionmentioning
confidence: 89%
“…Specifically, we have described that ouabain (1) boosts intercellular connections facilitated by tight junctions, as proven by an increase in transepithelial electrical resistance (TER), a simultaneous decrease in the movement of dextran between cells, and an increase in the expression of claudins 1, 2, and 4 [13]; (2) induces alterations in adherens junctions, resulting in heightened expression of E-cadherin, β-catenin, and γ-catenin [14]; (3) fosters the enhancement of gap junctional communication among cells forming fully developed epithelial monolayers [15] by modifying the distribution of Cx32 and Cx43 within the membrane [16]; and (4) expedites the recovery of the epithelial phenotype in cells seeded at confluence after trypsinization, as indicated by the presence of an apical cilium in MDCK cells [17]. Apart from its involvement in regulating intercellular contact components, we have found that ouabain also influences the expression of voltage-gated potassium channels, entailing Na + /K + -ATPase acting as a receptor and the engagement of multiple signaling pathways, including cSrc, PI3K, Erk1/2, NF-κB, and β-catenin [18].…”
Section: Introductionmentioning
confidence: 89%
“…It has also been shown that in all of these effects induced by ouabain, NKA functions as a receptor, initiating various signaling pathways. For cell-cell induced effects, a signaling pathway involving SRC/RAS/RAF/MEK/ERK is implicated, while ion current en- Moreover, electrophysiological assays (whole-cell patch clamp) demonstrate that in MDCK cells organized as epithelial monolayers, nanomolar doses of ouabain induce the expression of ionic currents attributed to the presence of voltage-gated potassium channels (IKv) [243] alongside ionic currents associated with the presence of TRPV4 channels (ITRPV4) [244].…”
Section: Nka Is a Receptor Of Cgs That Regulates The Epithelial Pheno...mentioning
confidence: 99%
“…Moreover, electrophysiological assays (whole-cell patch clamp) demonstrate that in MDCK cells organized as epithelial monolayers, nanomolar doses of ouabain induce the expression of ionic currents attributed to the presence of voltage-gated potassium channels (IKv) [ 243 ] alongside ionic currents associated with the presence of TRPV4 channels (ITRPV4) [ 244 ].…”
Section: Nka In Epithelial Physiologymentioning
confidence: 99%
See 2 more Smart Citations

Na+/K+-ATPase: More than an Electrogenic Pump

Contreras,
Torres-Carrillo,
Flores-Maldonado
et al. 2024
IJMS
Self Cite